2010
DOI: 10.1096/fj.09-147447
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1receptors (A1Rs) play a critical role in osteoclast formation and function

Abstract: Adenosine regulates a wide variety of physiological processes via interaction with one or more G-protein-coupled receptors (A(1)R, A(2A)R, A(2B)R, and A(3)R). Because A(1)R occupancy promotes fusion of human monocytes to form giant cells in vitro, we determined whether A(1)R occupancy similarly promotes osteoclast function and formation. Bone marrow cells (BMCs) were harvested from C57Bl/6 female mice or A(1)R-knockout mice and their wild-type (WT) littermates and differentiated into osteoclasts in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 68 publications
5
79
1
1
Order By: Relevance
“…Pellegatti et al (2011) reported that the A1 receptor was only weakly expressed by osteoclasts and activation of the A1 receptor was recently shown to have no effect on mouse osteoclasts (Pellegatti et al, 2011;He et al, 2012). In contrast, blockade or deletion of the A1 receptor can reduce the formation of mouse osteoclasts in culture (Kara et al, 2010a) and A1 receptor knockout mice display increased bone mineral density and resistance to ovariectomy-induced bone loss (Kara et al, 2010b) Adenosine has also been reported to stimulate osteoclastogenesis indirectly. Evans et al (2006) suggested that the adenosine produced from the hydrolysis of released ATP acts on P1 receptors to cause IL-6 release and inhibition of osteoprotegerin secretion (Evans et al, 2006).…”
Section: P1 Receptors Adenosine and Osteoclastsmentioning
confidence: 99%
“…Pellegatti et al (2011) reported that the A1 receptor was only weakly expressed by osteoclasts and activation of the A1 receptor was recently shown to have no effect on mouse osteoclasts (Pellegatti et al, 2011;He et al, 2012). In contrast, blockade or deletion of the A1 receptor can reduce the formation of mouse osteoclasts in culture (Kara et al, 2010a) and A1 receptor knockout mice display increased bone mineral density and resistance to ovariectomy-induced bone loss (Kara et al, 2010b) Adenosine has also been reported to stimulate osteoclastogenesis indirectly. Evans et al (2006) suggested that the adenosine produced from the hydrolysis of released ATP acts on P1 receptors to cause IL-6 release and inhibition of osteoprotegerin secretion (Evans et al, 2006).…”
Section: P1 Receptors Adenosine and Osteoclastsmentioning
confidence: 99%
“…Recent studies in our laboratory have revealed a novel role for adenosine/A 1 receptor (A 1 R) in osteoclastogenesis: A 1 R activation is required for both osteoclast formation and function in vitro and only function in vivo, as demonstrated using pharmacologic inhibitors and mice lacking adenosine A 1 receptors [29,30]. The disparity between in vitro and in vivo osteoclast formation is reminiscent of a similar disparity in osteoclast formation in vitro and in vivo in mice lacking either TRAF6 or Atp6v0d2 in which osteoclasts are present in vivo, although functionally defective [31] and do not form from precursors in vitro [32,33]).…”
Section: Introductionmentioning
confidence: 99%
“…For example, A 2A receptor agonists have been shown to both inhibit [33] and stimulate [25] the formation and activity of osteoclasts. Kara and colleagues [51] found that A 1 receptor antagonists decreased osteoclast formation and resorption. However, we found that mouse osteoclasts only express low levels of A 1 receptor protein.…”
Section: Discussionmentioning
confidence: 99%